Quantitative Data-driven Utilization of Hematologic Labs Following Lumbar Fusion. Issue 4 (May 2015) - Yew, Andrew Y.; Hoffman, Haydn; Li, Charles; McBride, Duncan Q.; Holly, Langston T.; Lu, Daniel C.
Abstract : Study Design: Retrospective case series. Summary of Background Data: Large national inpatient databases estimate that approximately 200, 000 lumbar fusions are performed annually in the United States alone. It is common for surgeons to routinely order postoperative hematologic studies to rule out postoperative anemia despite a paucity of data to support routine laboratory utilization. Objective: To describe quantitative criteria to guide postoperative utilization of hematologic laboratory assessments. Methods: A retrospective analysis of 490 consecutive lumbar fusion procedures performed at a single institution by 3 spine surgeons was performed. Inclusion criteria included instrumented and noninstrumented lumbar fusions performed for any etiology. Data were acquired on preoperative and postoperative hematocrit, platelets, and international normalized ratio as well as age, sex, number of levels undergoing operation, indication for surgery, and intraoperative blood loss. Multivariate logistic regression was performed to determine correlation to postoperative transfusion requirement. Results: A total of 490 patients undergoing lumbar fusion were identified. Twenty-five patients (5.1%) required postoperative transfusion. No patients required readmission for anemia or transfusion. Multivariate logistic regression analysis demonstrated that reduced preoperative hematocrit and increased intraoperative blood loss were independent predictors of postoperative transfusion requirement. Intraoperative blood loss >1000 mL had an odds ratio of 8.9 ( P =0.013), and preoperative hematocrit <35 had an odds ratio of 4.37 ( P =0.008) of requiring a postoperative transfusion. Conclusions: Routine postoperative hematologic studies are not necessary in many patients. High intraoperative blood loss and low preoperative hematocrit were independent predictors of postoperative blood transfusion. Our results describe quantitative preoperative and intraoperative criteria to guide data-driven utilization of postoperative hematologic studies following lumbar fusion.